IMPLEMENTASI KURIKULUM 2013 DALAM PEMBELAJARAN KIMIA KELAS X SMA SE-KOTA JAYAPURA - TEGUH IMAN SANTOSA; TIURLINA SIREGAR (Program Magister Pendidikan IPA, Program Pascasarjana Universitas Cenderawasih, 2018)
This study aimed to evaluate the feasibility of learning applied chemistry teacher of class X associated with the implementation of Curriculum 2013 in the schools, the results of the analysis of these implementations will be referred to the standardization that has been set by the Minister of Education as a reference implementation of Curriculum 2013. This type of research is research qualitative evaluative. The method or technique of collecting data is interactive and non-interactive. Results of the study subjects chemistry class X Curriculum 2013 are guided by the Permendikbud No. 59 of 2014, Permendikbud No. 103 of 2014 and Permendikbud No. 104 2014 shows (1) In the learning plan can be implemented and supported by the results of the questionnaire teachers who achieve 86% success rate (2) Implementation of the learning can be implemented and supported by the results of the questionnaire teachers who achieve 86% success rate. (3) the learning process can be accomplished in accordance with and supported by the results of the questionnaire teachers who achieve 81% success rate. (4) Assessment of learning outcomes can be accomplished and supported by the results of the questionnaire teachers who achieve 87% success rate. The results showed that the implementation of the curriculum in 2013 subjects chemistry class X as determined by Permendikbud No. 59 of 2014, Permendikbud No. 103 of 2014 and No. 104 Permendikbud 2014.